A tailspike with exopolysaccharide depolymerase activity from a new Providencia stuartii phage makes multidrug-resistant bacteria susceptible to serum-mediated killing - Oliveira, Hugo Alexandre Mendes (2020)
Providencia stuartii is emerging as a significant drug-resistant nosocomial pathogen, which encourages the search for alternative therapies. Here, we have isolated Providencia stuartii phage Stuart, a novel podovirus infecting multidrug-resistant hospital isolates of this bacterium. Phage Stuart is a proposed member of a new Autographivirinae subfamily genus, with a 41,218-bp genome, direct 345-bp repeats at virion DNA ends, and limited sequence similarity of proteins to proteins in databases. Twelve out of the 52 predicted Stuart proteins are virion components. We found one to be a tailspike with depolymerase activity. The tailspike could form a highly thermostable oligomeric Î²-structure migrating close to the expected trimer in a nondenaturing gel. It appeared to be essential for the infection of three out of four P. stuartii hosts infected by phage Stuart. Moreover, it degraded the exopolysaccharide of relevant phage Stuart hosts, making the bacteria susceptible to serum killing. Prolonged exposure of a sensitive host to the tailspike did not cause the emergence of bacteria resistant to the phage or to serum killing, opposite to the prolonged exposure to the phage. This indicates that phage tail-associated depolymerases are attractive antivirulence agents that could complement the immune system in the fight with P. stuartii.IMPORTANCE The pace at which multidrug-resistant strains emerge has been alarming. P. stuartii is an infrequent but relevant drug-resistant nosocomial pathogen causing local to systemic life-threatening infections. We propose an alternative approach to fight this bacterium based on the properties of phage tailspikes with depolymerase activity that degrade the surface bacterial polymers, making the bacteria susceptible to the immune system. Unlike antibiotics, phage tailspikes have narrow and specific substrate spectra, and by acting as antivirulent but not bactericidal agents they do not cause the selection of resistant bacteria.